Answer: the answer is number four.
Step-by-step explanation:
<h2>because when you take five multiply by A (5*a) you will get 5a and when you take five multiply by six (5*6) you will get 30 and there is positive sign so the plus (+) stays the same and your will be (5a+30) that is your answer. good luck.</h2>
Answer:
51
Step-by-step explanation:
The last name I am pretty sure of it.
Answer:
x = -1/2 x=-1
Step-by-step explanation:
2x( x+1.5) = -1
Distribute
2x^2 + 3x = -1
Add 1 to each side
2x^2 +3x+1 = 0
Factor
(2x+1) (x+1) =0
Using the zero product property
2x+1 = 0 x+1=0
2x = -1 x=-1
x = -1/2 x=-1
Answer:
3(k - 1)² = 12
Step-by-step explanation:
To complete the square, write the equation standard form and make the a term's coefficient 1.
3k² = 11 + 6k
3k² - 6k - 11 = 0
3(k² - 2k) = 11
Take the middle term -2k and divide the coefficient in 2 and square it. Here it is -2/2 = -1. -1² = 1. Add 1 to both sides.
3(k² - 2k + 1) = 11 + 1
3(k - 1)² = 12